Fireweed (Heartleaf nettle) Control in Pastures - Jason A. Ferrell (EDIS)
Fireweed (Urtica chamaedryoides) (Figure 1) is native to Florida, but has only recently become problematic. This winter annual species is commonly observed in north and central Florida pastures, particularly in bareground areas (near feeding pens and under fences) as well as along tree lines where forage grasses are less dense. It is particularly troublesome because it possesses stinging hairs that easily embed in skin. Once exposed to the toxin, severe irritation can occur for several hours. This document is SS-AGR-41, one of a series of the Agronomy Department, UF/IFAS Extension. Original publication date May 2006. Reviewed November 2006.